Conducive target range of breast cancer: Hypoxic tumor microenvironment - Cheng, Wen; Xiao, Xian; Liao, Yang; Cao, Qingqing; Wang, Chaoran; Li, Xiaojiang; Jia, Yingjie (Frontiers in Oncology, 2022)
Breast cancer is a kind of malignant tumor disease that poses a serious threat to human health. Its biological characteristics of rapid proliferation and delayed angiogenesis, lead to intratumoral hypoxia as a common finding in breast cancer. HIF as a transcription factor, mediate a series of reactions in the hypoxic microenvironment, including metabolic reprogramming, tumor angiogenesis, tumor cell proliferation and metastasis and other important physiological and pathological processes, as well as gene instability under hypoxia. In addition, in the immune microenvironment of hypoxia, both innate and acquired immunity of tumor cells undergo subtle changes to support tumor and inhibit immune activity. Thus, the elucidation of tumor microenvironment hypoxia provides a promising target for the resistance and limited efficacy of current breast cancer therapies. We also summarize the hypoxic mechanisms of breast cancer treatment related drug resistance, as well as the current status and prospects of latest related drugs targeted HIF inhibitors.